Urgent care for older people. (23rd February 2021) - Conroy, Simon; Thomas, Matt
Abstract: Geriatric medicine is the clinical specialty that focuses upon the care of older people—especially those with frailty (a state of increased vulnerability). In hospital, older people living with frailty are at high risk of developing a range of unpleasant outcomes such as delirium, falls, fractures, pressure sores and death. Comprehensive geriatric assessment is a form of holistic care that incorporates a specific set of clinical competencies that are able to reduce these adverse outcomes. Over the years, geriatric medicine has moved from being more of a community-based service towards a more acute specialty—encroaching now upon emergency department care. The challenge now is to work out how best to deliver geriatric care across the whole hospital (older people with frailty are not just cared for in geriatric wards!). The themed collection published on the Age & Ageing journal website outlines key articles that are attempting to develop solutions to this challenging conundrum. We hope that you enjoy reading them.